Molecular characterisation of carbapenem-resistant Klebsiella pneumoniae clinical isolates: preliminary experience from a tertiary care teaching hospital in the Himalayas. (13th January 2022) - Bhatia, Mohit; Shamanna, Varun; Nagaraj, Geetha; Sravani, Dharmavaram; Gupta, Pratima; Omar, Balram Ji; Chakraborty, Deepika; Ravikumar, K L
Abstract: Background: There is a lack of whole-genome sequencing (WGS) data on multidrug-resistant (MDR) bacteria from the Uttarakhand region of India. The aim of this study was to generate WGS data of carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates recovered from patients in Uttarakhand's tertiary care centre. Methods: A cross-sectional study included 29 MDR K. pneumoniae test isolates obtained from various clinical samples submitted to the bacteriology laboratory for culture and sensitivity testing from July 2018 to August 2019. After preliminary identification and antibiotic susceptibility testing, these isolates were subjected to WGS. Results: A total of 27 of 29 isolates were CRKP. ST14 was the most common sequence type (n=8 [29.6%]). Carbapenem resistance was mainly encoded by OXA-48-like genes (21/27 [77.8%]). All isolates had a varied arsenal of resistance genes to different antibiotic classes. KL2 (9/27 [33.3%]) and KL51 (8/27 [29.6%]) were dominant K loci types. O1 and O2 together accounted for 88.9% (n=27) of CRKP isolates. Genes encoding yersiniabactin ( ybt ) and aerobactin ( iuc ) were identified in 88.9% (24/27) and 29.6% (8/27) of isolates. The predominant plasmid replicons present were ColKP3 (55.5%), IncFII(K) (51.8%) and IncFIB(pQil) (44.4%). Conclusions: This study emphasises the need for continued genomic surveillance of MDR bacteria that could be instrumental in developing treatment guidelines based on integrating phenotypic and molecular methods.